1999
DOI: 10.1152/jn.1999.81.6.3065
|View full text |Cite
|
Sign up to set email alerts
|

Mesial Motor Areas in Self-Initiated Versus Externally Triggered Movements Examined With fMRI: Effect of Movement Type and Rate

Abstract: The human frontomesial cortex reportedly contains at least four cortical areas that are involved in motor control: the anterior supplementary motor area (pre-SMA), the posterior SMA (SMA proper, or SMA), and, in the anterior cingulate cortex, the rostral cingulate zone (RCZ) and the caudal cingulate zone (CCZ). We used functional magnetic resonance imaging (fMRI) to examine the role of each of these mesial motor areas in self-initiated and visually triggered movements. Healthy subjects performed self-initiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
236
5
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 392 publications
(272 citation statements)
references
References 58 publications
27
236
5
4
Order By: Relevance
“…For instance, the ventral limit of pre-SMA was at z = 33, the ventral limit where SMA intersects the VCA line was at z = 40, and the ventral limit of SMA proper was at z = 44. Therefore, our data suggest that the ventral limit is more ventral rostrally than it is caudally, and this finding is consistent with previous depictions (in figures) (Crosson et al, 1999;Deiber et al, 1999;Johansen-Berg et al, 2004). It is interesting to note that these values were ventral to the location of the cingulate sulcus in the Talairach and Tournoux atlas (1988).…”
Section: Ventral Limit Of Mpmcsupporting
confidence: 92%
See 3 more Smart Citations
“…For instance, the ventral limit of pre-SMA was at z = 33, the ventral limit where SMA intersects the VCA line was at z = 40, and the ventral limit of SMA proper was at z = 44. Therefore, our data suggest that the ventral limit is more ventral rostrally than it is caudally, and this finding is consistent with previous depictions (in figures) (Crosson et al, 1999;Deiber et al, 1999;Johansen-Berg et al, 2004). It is interesting to note that these values were ventral to the location of the cingulate sulcus in the Talairach and Tournoux atlas (1988).…”
Section: Ventral Limit Of Mpmcsupporting
confidence: 92%
“…These two regions have been previously differentiated in the monkey (Dum and Strick, 1991;Matelli et al, 1991;Matsuzaka et al, 1992). Since then, this demarcation has been supported in humans across studies using cytoarchitectonic data (Vorobiev et al, 1998;Geyer et al, 2000a), PET (Fink et al, 1997), functional MRI (Deiber et al, 1999), diffusion tensor imaging , and diffusion weighted imaging (Johansen-Berg et al, 2004). The boundary between pre-SMA and SMA proper estimated by the ALE method remained consistent at y = 0mm throughout the coronal plane (Fig.…”
Section: Pre-sma Vs Sma Propersupporting
confidence: 53%
See 2 more Smart Citations
“…This study reported different pattern of response in the supplementary motor area (SMA) of patients as compared to controls, and higher asymmetry index. This area is responsible for preparation and execution of movements and participates in the control of posture [29,30]. The authors, therefore, hypothesized that a defective sensorimotor integration at cortical level plays a role in IS pathogenesis.…”
Section: Discussionmentioning
confidence: 99%